El arte en la educación de la primera infancia: una necesidad impostergable - Luzmila Mendívil Trelles de Peña (Pontificia Universidad Católica del Perú, 2011)
Art in early childhood education: An ineluctable need The present essay focuses on the need for educational institutions, especially those working with early childhood, to recover art as a central issue in the education of young children, both in relation to the demands of the new century demands, as well in response to the most authentic needs of every human being. It also addresses the role of art in the development of inherent capacities not only to individual areas, linked to creativity, imagination, and the development of the scientific attitude, but those of social nature that include the construction of personal and cultural identity, as well as the skills required to live with others, and those leading to social change.